2011
DOI: 10.3346/jkms.2011.26.6.701
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Panic Disorder

Abstract: Panic disorder is one of the chronic and disabling anxiety disorders. There has been evidence for either genetic heterogeneity or complex inheritance, with environmental factor interactions and multiple single genes, in panic disorder's etiology. Linkage studies have implicated several chromosomal regions, but no research has replicated evidence for major genes involved in panic disorder. Researchers have suggested several neurotransmitter systems are related to panic disorder. However, to date no candidate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…87 Future studies should attend to entire genetic regions and take a syndrome approach by expanding phenotype definitions beyond diagnostic criteria of single disorders to include multiple common comorbid medical and psychiatric conditions. 48,56,84,88,89 Consistent with a syndrome model, migraine and anxiety have been associated with the serotonin transporter gene 5-HTTLPR polymorphism. 90 Several studies have reported a genetic linkage between anxiety disorders such as PD and various medical conditions (eg, migraine, chronic headache, mitral valve problems) evident around the region of chromosome 13.…”
Section: Potential Mechanisms Of Comorbiditymentioning
confidence: 88%
See 2 more Smart Citations
“…87 Future studies should attend to entire genetic regions and take a syndrome approach by expanding phenotype definitions beyond diagnostic criteria of single disorders to include multiple common comorbid medical and psychiatric conditions. 48,56,84,88,89 Consistent with a syndrome model, migraine and anxiety have been associated with the serotonin transporter gene 5-HTTLPR polymorphism. 90 Several studies have reported a genetic linkage between anxiety disorders such as PD and various medical conditions (eg, migraine, chronic headache, mitral valve problems) evident around the region of chromosome 13.…”
Section: Potential Mechanisms Of Comorbiditymentioning
confidence: 88%
“…Future studies should attend to entire genetic regions and take a syndrome approach by expanding phenotype definitions beyond diagnostic criteria of single disorders to include multiple common comorbid medical and psychiatric conditions . Consistent with a syndrome model, migraine and anxiety have been associated with the serotonin transporter gene 5‐HTTLPR polymorphism .…”
Section: Potential Mechanisms Of Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of anxiety symptoms on the survival of patients with CAD is still controversial (1,9Y15). Besides, there are studies showing that ethnicity and culture are important factors in shaping psychopathology and pharmacotherapeutic responses in patients with anxiety (16,17). Whether these differences could result in different cardiovascular outcomes in different ethnicities is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings have not been consistently replicated and no specific susceptibility loci have been established. [27][28][29] Thus, a genome-wide association approach is increasingly being used to delineate such loci. 30,31 Additional, genome-wide association studies in larger population samples, as well as gene-environment interaction studies, are needed to confirm preliminary results.…”
Section: Pathogenesis Of Panic Disordermentioning
confidence: 99%